2022
DOI: 10.3892/ijmm.2022.5108
|View full text |Cite
|
Sign up to set email alerts
|

TGF‑β1 affects the renal cancer miRNome and regulates tumor cells proliferation

Abstract: TGF-β1 is a pleiotropic cytokine that can either promote or inhibit cancer development and progression. It was previously found that TGF-β1 can regulate the expression of several microRNAs (miR or miRNA) involved in the progression of renal cell carcinoma (Rcc). Therefore, the present study aimed to analyze the effects of TGF-β1 on the global Rcc miRNome. It was found that TGF-β1 can regulate a complex network consisting of miRNAs and mRNAs involved in Rcc transformation. In particular, TGF-β1 was revealed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
2
9
0
Order By: Relevance
“…Previous studies indicated that TGF‐β1 played a crucial role in the transformation of MSCs to CAFs in various cancers (Xiong et al, 2020). In a case, it was reported that the TGF‐β1 signaling pathway was abnormally activated in the ccRCC cells (Hanusek et al, 2022). Similarly, our analysis of KIRC data in the TCGA database indicated that the TGF‐β1 expression level was significantly higher in the KIRC tumor tissues than in the paracancerous tissues (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that TGF‐β1 played a crucial role in the transformation of MSCs to CAFs in various cancers (Xiong et al, 2020). In a case, it was reported that the TGF‐β1 signaling pathway was abnormally activated in the ccRCC cells (Hanusek et al, 2022). Similarly, our analysis of KIRC data in the TCGA database indicated that the TGF‐β1 expression level was significantly higher in the KIRC tumor tissues than in the paracancerous tissues (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…Also, miR-181b-5p encapsulated in tumor-derived extracellular vesicles could affect angiogenesis to promote the tumorigenesis and metastasis of esophageal squamous cell carcinoma (Wang et al, 2020). In the study of RCC, TGF-β1 affected the expression of miR-181b-5p to regulate the proliferation and progression of RCC (Hanusek et al, 2022). Also, miR-181b-5p was upregulated by circular RNA circCSNK1G3 to promote tumor growth and metastasis in RCC via the TIMP3-mediated epithelial-to-mesenchymal transition (EMT) process (Li et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcription and qPCR were performed as described previously [ 10 ]. The sequences of the primers used in the study are presented in Additional file 1 : Table S2.…”
Section: Methodsmentioning
confidence: 99%